Kontruksi Gender dan Representasi Aktor Sosial dalam Drama “Lutung Kasarung”: Analisis Wacana Kritis Theo Van Leeuwen - Sitti Nurazisa Zainuddin; Muhammad Akhir; Maria Ulviani (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The article entitled “Gender Construction and Representation of Social Actors in the Drama Lutung Kasarung: A Critical Discourse Analysis by Theo van Leeuwen” aims to describe the representation of gender-based social actors through inclusion and exclusion strategies and to reveal the construction of gender ideology built in the drama text. This study uses a qualitative approach with a descriptive-analytical design. The research data source is the drama text Lutung Kasarung, while the analysis unit includes dialogue, narrative, and the depiction of characters who represent gender-based social actors. Data collection techniques are carried out through documentation by reading, identifying, and grouping data according to Theo van Leeuwen's analysis categories. The results of the study show that the inclusion strategy is more dominantly used to present male characters as strong, rational figures, and have authority in determining the course of the story. In contrast, female characters are represented in two patterns, namely the ideal passive woman and the dominant woman who is constructed negatively. In addition, the exclusion strategy is used to obscure the role of women in decision-making, thereby reinforcing gender marginalization. This study concludes that the drama Lutung Kasarung represents patriarchal ideology through discourse practices that shape power relations between men and women.